Students to do research in Belum - Temengor forest - New Sarawak, Tribune (New Sarawak Tribune, 2012)
KUALA LUMPUR: Two universities yesterday signed a memorandum of understanding with the Pulau Banding Foundation (PBF) to enable their students to conduct research in the 130 million year old Belum Temengor forest in Hulu Perak.